Integrating Diversified Graphical Thinking Mode into the Teaching Practice of Inorganic Chemistry - Shen, Qing-Kun; Ren, Qun-Xiang; Sui, Li-Li; Luan, Tian; Wang, Jin (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Inorganic chemistry holds significant importance in pharmacy major as it serves as the foundation for subsequent professional courses. However, students exhibit varying learning conditions during the teaching process, with some struggling due to weak knowledge of chemistry. Objectives: To enhance the quality of teaching and learning outcomes, foster logical thinking skills and independent learning abilities among students and further promote the exploration and implementation of reforms in inorganic chemistry education. This study aims to integrate diverse graphical thinking modes into inorganic chemistry teaching practices, guiding students to simplify and visualize knowledge through graphical thinking. Materials and Methods: Based on the course design, various diversified graphic thinking modes are introduced into teaching practices, followed by a comparative analysis and questionnaire survey to evaluate their impact on teaching effectiveness and student satisfaction. Results: The experimental group achieved an average score of 12.1 points higher than that of the control group (p<0.01). Moreover, satisfaction surveys reveal significantly higher levels of satisfaction among 96.4% of students from the experimental group compared to 83.6% from the control group using traditional teaching methods (p<0.05). Additionally, a survey assessing acceptability among students in the experimental group yielded satisfactory responses ranging from 81.8-94.5% across all 10 questions. Conclusion: Incorporating diversified graphical thinking modes into the inorganic chemistry teaching process can improve academic performance and interest while enhancing overall teaching effectiveness, thus providing valuable insights for developing diversified instructional approaches.
Keywords: Graphic thinking mode; Inorganic chemistry; Teaching strategy; Chemical teaching; Higher education.